MODEL PENGATURAN HUKUM PIDANA TERHADAP PENGGUNA JASA PEKERJA SEKS KOMERSIAL DI INDONESIA - Leni Fuji Lestari; Erdianto '; Ferawati ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Prostitution is a job that a person who acts as an intermediary or service provider (pimps), commercial sex workers, and service users themselves. Commercial sex work is not only carried out by people who do it down the middle to meet the necessities of life, in fact, recently we see and listen to the news that public figures, though there have been many who undergo job These just to get more money. If seen from the legitimacy of the law, the service user can not be subject to criminal terbenturnya because the law enforcement in Indonesia with the legal principle of